KETIDAKMAMPUAN PEMECAHAN SOAL HUKUM ARCHIMEDES BERDASARKAN TAKSONOMI STRUCTURE OF THE OBSERVED LEARNING OUTCOME SISWA SMA - F03110023, Annisa Rahman; Sutrisno, Leo; ., Hamdani (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2014)
Abstract: Simple descriptive survey method was conducted to investigate the percentage of students who were not able to solve Archimedes Law problems and reveal the forms of the inability which were experienced by students in each level of SOLO taxonomy. Using intact group method, 85 students from three classes were chosen to be the participants in this study. Data was collected by using 4 essay tests,concerning: (1) buoyant force concept application, (2) buoyant force on floating object, (3) buoyant force on submerged object, (4) buoyant force on drowned object. Eachtest consists of four questions that represented each level of SOLO taxonomy. It was found that 48,2% students were not able to solve questions on uni-structural level; 78,8% students were not able to solvequestions on multi-structural level; 97,6% students were not able to solve questions on relational level and 100% students were not able to solvequestions on extended abstract level. The problems concerning buoyant force on drowned objects was the problem which most student unable to solve (95,3%). The most form of the inability which were experienced by students was not able to use the correct formula (30,7%). It is suggested that the further study to conduct a treatment particularly to improve students’ physics problem solving ability at extended abstract level. Keywords : Archimedes Law, SOLO Taxonomy Abstrak: Penelitian ini bertujuan untuk mengetahui persentase jumlah siswa yang tidak mampu memecahkan soal hukum Archimedes serta mengungkap bentuk-bentuk ketidakmampuan yang dialami pada tiap level taksonomi SOLO. Untuk itu, digunakan metode survei berbentuk deskriptif sederhana yang melibatkan 85 siswa kelas XI SMA Negeri 8 Pontianak tahun pelajaran 2013/2014. Alat pengumpul menggunakan 4 buah soal pada konsep (1) gaya apung, (2) fenomena terapung, (3) fenomena melayang dan (4) fenomena tenggelam, dengan tiap soal terdiri dari empat pertanyaan pada tiap level taksonomi SOLO. Ditemukan 48,2% siswa tidak mampu memecahkan soal level uni-structural; 78,8% siswa tidak mampu memecahkan soal level multi-structural; 97,6% siswa tidak mampu memecahkan soal level relational dan 100% siswa tidak mampu memecahkan soal level extended abstract dengan bentuk ketidakmampuan yang paling banyak dialami yaitu tidak mampu menggunakan rumus yang tepat (30,7%). Soal mengenai konsep fenomena tenggelam merupakan soal yang paling banyak tidak mampu dipecahkan oleh siswa (97,3%). Disarankan agar dilakukan penelitian lebih lanjut guna meningkatkan kemampuan siswa dalam memecahkan soal fisika khususnya pada level extended abstract. Kata Kunci : Hukum Archimedes, Taksonomi SOLO